Comparison of patients' age receiving therapeutic services in a cleft care team in Isfahan - Saeed Soheilipour; Fatemeh Soheilipour; Fatemeh Derakhshandeh; Hedieh Hashemi; Mehrdad Memarzadeh; Hamid Salehiniya; Fahimeh Soheilipour (Wolters Kluwer Medknow Publications, 2016)
Background: Due to numerous difficulties in patients suffering from varieties of cleft lip and palate, their therapeutic management involves interdisciplinary teamwork. This study was conducted to compare the age of commencing treatments such as speech therapy, secondary palate and alveolar bone grafting and orthodontics between those who sought treatment early and late. Materials and Methods: In this retrospective study, 260 files of patients with cleft lip and palate based on their age at the time of admission to a cleft care team were divided into two groups: The early admission and late admission. Both groups compared based on four variables including the mean age of beginning speech therapy, palatal secondary surgery, alveolar bone grafting, and receiving orthodontics using t-test. Results : Based on the results, among 134 patients admitted for speech therapy, the mean age of initiating speech therapy in early clients was 3.3 years, and in the late ones was 9 years. Among 47 patients with secondary surgery, the mean age in early clients was 3.88 years, and in the late clients was 15.7 years. Among 17 patients with alveolar bone grafting, the mean age in the first group was 9 years, and in the other was 16.69 years. Among 24 patients receiving orthodontic services, the mean age in early clients was 7.66 years, and in the second group was 17.05 years. Conclusion: There was a significant difference between the age of performing secondary surgery and alveolar bone grafting and the age of beginning speech therapy and receiving orthodontic services in early references and late references to the team.